Synthesis, Characterization, X-Ray Single-Crystal Structure, Potentiometric Measurements, Molecular Modeling, and Bioactivity Screening of Some Thiosemicarbazones - Abeer A. El-Sisi; Mohamed Ali; Sohair F. Ramdan; Osama AlTaweel; Ahmed I. A. Abd El-Mageed; Ahmed A. El-Sherif (Journal of Chemistry)
A series of thiosemicarbazone (TSCN) compounds including ((E)-2-((E)-1-(2-(p-tolyl)hydrazono)propan-2-ylidene)hydrazine-1-carbothioamide (TSC1), (E)-N-ethyl-2-((E)-1-(2-(p-tolyl)hydrazono)propan-2-ylidene)hydrazine-1-carbothioamide (TSC2), and (E)-N-phenyl-2-((E)-1-(2-(p-tolyl)hydrazono)propan-2-ylidene)hydrazine-1-carbothioamide) (TSC3) were synthesized and fully characterized by diverse spectroscopies, such as X-ray single-crystal, infrared, mass, proton nuclear magnetic resonance, and ultraviolet-visible. Potentiometric measurements, molecular modeling, and biological and antitumor activity screening were studied. The thermodynamics and protonation constants of TSC1 as a representative of the synthesized TSCs were calculated and discussed. The solution speciation of different species was studied with pH. The molecular parameters of the optimized structures were calculated and discussed. The X-ray single crystals of TSC2 and TSC3 were established. Considering the antimicrobial activities and correlating structure-activity relationship of the synthesized compounds, the TSC1 molecule was considered a promising candidate as an antifungal agent against Candida albicans. Thus, it would be extremely helpful in the field of medicinal chemistry, particularly as an antimicrobial agent. The results are of significance to the chemistry of antimicrobial agents.